PENGARUH MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR MAHASISWA STUDI KASUS PADA PROGRAM STUDI TEKNIK SIPIL INSTITUT SAINS DAN TEKNOLOGI AL KAMAL JAKARTA - Setyorini, Desy (EDUTECH CONSULTANT, 2018)
This research was conducted to obtain the influence of the independent variable motivation with the student learning achievement as dependent variable by taking 70 sample in the population of Institut Sains dan Teknologi Al Kamal Jakarta which consisted of 70 people who had given its input through the questionnaire provided researchers and measured by likert scale use correlation and regression to hypothesis .The result analysis of the data and test hypotheses are ( 1 ) the value a sig . With 2-tailed ( 0.253 ) as much as to the level of a very strength mean so much smaller than the level of significant(Î±) 1 % and value of r2 or coefficient of determination as much as 0.640 , so it can be concluded that h1 accepted which means hypothesis advanced by tested that the impact of which is between the motivation with the student learning achievemet. The conclusion of this research is motivation,having significant influence with student learning achievement from Institut Sains and teknologi Al Kamal Jakarta.